Prácticas de normas de bioseguridad en el personal de salud del servicio de Gineco-Obstetricia del hospital General Isidro Ayora - Peláez Cartuche, Gina Pamela (2015)
The rules of biosecurity are a set of measures lead to keep the control of the occupational hazard which come from biological, chemical agents and others, for that reason it is important that the health personal know, practice and accomplish those rules, by this way their health and security will be in save during the development of their activities. It was done a descriptive study. The present study identifies the full fill the biosecurity rules to avoid the occupational hazard by exposition to biological and chemical agents in the health members who work in the Gineco-Obstetricia Service of Isidro Ayora General Hospital of Loja CITY; to collect the information it was used as a technique the survey, it was applied to 71 professional of the health who work in the Gineco-obstetricia service; the results demonstrate that, the accomplishment of the biosecurity rules to avoid rhe occupational hazard by exposition to biological agents in the health personal is medium. It is due that the half of the members accomplish with preventive measures like washing hands, use of elements of personal protection (lab coat, gloves, apron and protector glasses), adequate manage of hurts and updating of the vaccination schedule. In regard to the biosecurity rules, it is important to avoid occupational hazard by exposition to chemical agents. It was determined that anyone of the members of the personal who participated in the research got an optimal fulfillment, emphasizing that only one less percentage has received information about the chemical existing products in the service and their risks, in addition they do not do an adequate classification of those products, and the most worrying aspect in that Health Center is that people do not use labs and masks in the manage of them. Key words: Biological agents, chemical agents, rules of biosecurity.